(untitled) (The Journal of Psychology and Sociology, 2017)
This article analyzes the role of psychological training in work with divorced spouses. The relevance and timeliness of the study is due to prevailing contradiction between objective need for the implementation of psychosocial support and assistance to the family members in a situation of divorce and insufficient development in domestic psychological literature and practice of methodological frameworks and tools to implement them. The results of the experimental research of dialogic interaction between divorced spouses and a psychologist in the conditions of specially organized psychological training, allow to consider this form of work as a condition for coping with postdivorced crisis. So, the results of the study showed that in the course of psychological training it is possible in a relatively short time to solve the problem of intense formation and development of relevant skills and knowledge. The study authors found that participation in specially organized training led to higher success rates of postdivorced coping, and, as a consequence, to improve the performance of physical and mental health of divorced people.